2013
DOI: 10.1007/978-1-4471-4911-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Chalcogenides for Oxygen Reduction

Abstract: Chalcogenide materials are considered as the promising catalysts for oxygen reduction reaction (ORR).1,2 However, their usage is hindered mainly by poor conductivity, which results a substantial decrease in activity upon cycling. Carbon supports such as vulcan and activated carbon generally used to increase the conductivity, but, the issue associated with the stability of the material still not solved. In this work, we have synthesized TM1xTM2yXz (TM = transition metal; X = S, Se, Te) nanoparticles with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…Typically it has been observed that changing from transition-metal oxide to transition-metal selenide leads to an increase of the conduction and valence band edges, making them closer to the water oxidation–reduction levels. The relative closeness of the band positions will expectedly lead to better charge transfer at the catalyst–electrolyte interface, thus enhancing the catalytic efficiency. Similar effect has been also reported by Alonso-Vante in a comprehensive report comparing the ORR activity of transition-metal chalcogenide catalysts where they have shown the favorable effect of selenization in increasing the ORR catalytic activity for both Pt-group metals as well other transition metals, especially Co . Similar effect has also been reported for Co 9 Se 8 through theoretical as well as experimental study .…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Typically it has been observed that changing from transition-metal oxide to transition-metal selenide leads to an increase of the conduction and valence band edges, making them closer to the water oxidation–reduction levels. The relative closeness of the band positions will expectedly lead to better charge transfer at the catalyst–electrolyte interface, thus enhancing the catalytic efficiency. Similar effect has been also reported by Alonso-Vante in a comprehensive report comparing the ORR activity of transition-metal chalcogenide catalysts where they have shown the favorable effect of selenization in increasing the ORR catalytic activity for both Pt-group metals as well other transition metals, especially Co . Similar effect has also been reported for Co 9 Se 8 through theoretical as well as experimental study .…”
supporting
confidence: 84%
“…20−22 The relative closeness of the band positions will expectedly lead to better charge transfer at the catalyst−electrolyte interface, thus enhancing the catalytic efficiency. Similar effect has been also reported by Alonso-Vante in a comprehensive report comparing the ORR activity of transition-metal chalcogenide catalysts where they have shown the favorable effect of selenization in increasing the ORR catalytic activity for both Pt-group metals as well other transition metals, especially Co. 23 Similar effect has also been reported for Co 9 Se 8 through theoretical as well as experimental study. 24 Additionally, these nonstoichiometric compositions such as Co 0.85 Se (i.e., Co 7 Se 8 ), being less Se rich and containing the metal in a mixed valent state, might be more beneficial for this kind of catalytic reactions because it can easily support variation of the metal oxidation state, thereby facilitating the reaction pathway.…”
mentioning
confidence: 99%
“…A possible path to solve the economic and geological constraints associated with the use of platinum when deploying PEMFCs consists in developing catalysts based on nonprecious metals. Many materials such as transition-metal oxides, nitrides, and/or carbides, transition-metal chalcogenides, nanostructured carbon materials, nitrogen-, sulfur-, boron-, and phosphorus-doped carbon materials, , and transition-metal/nitrogen/carbon (metal–NC) catalysts have been investigated for ORR electrocatalysis in acid and/or alkaline medium. Metal–NC catalysts synthesized by pyrolysis of a transition metal (Fe, Co), nitrogen and carbon precursors have demonstrated initial ORR activity approaching that of Pt/C in rotating disk electrode (RDE) or PEMFC. ,, Their ORR activity strongly depends on their physical and chemical structure, namely the nature and coordination of the metal centers, metal content, , redox potential, basicity of the N-containing groups, ,,, and pore size distribution in the carbon phase .…”
Section: Introductionmentioning
confidence: 99%
“…These include monometallic nanoparticles [4][5][6][7], alloy nanoparticles [8][9][10], metal oxides nanoparticles [11][12][13][14][15], and transition metal chalcogenide nanoparticles [16] that are supported on diverse substrates including metal structures [17], metal oxides [18], or carbon-based materials such as carbon black, standard carbon fibers [19], single-or multi-walled carbon nanotubes [20], and graphene sheets [21][22][23][24]. As summarized in several recent reviews [25][26][27], these supporting materials play important roles in, for instance, preventing nanoparticle aggregation and increasing the corresponding surface areas; manipulating electronic energy of the metal nanoparticles and hence interactions with O 2 molecules via intimate electronic interactions with the supporting substrates; enhancing electronic conductivity and serving as current collectors; as well as improving structural stability of the catalysts in extreme acidic or basic environments.…”
Section: Introductionmentioning
confidence: 99%